Seven days of nectar : contemporary oral performance of the Bhāgavatapurāṇa - Taylor, McComas, 1956- (Oxford University Press, 2016)
The thousand-year-old Sanskrit classic the Bhagavatapurana, or 'Stories of the Lord', is the foundational source of narratives concerning the beloved Hindu deity Krishna. For centuries pious individuals, families, and community groups have engaged specialist scholar-orators to give week-long oral performances based on this text. In recent years, these events have grown in number, scale, and popularity, filling vast public arenas, such as sports stadiums, and attracting live audiences in the tens of thousands while being simulcast around the world. In Seven Days of Nectar, McComas Taylor uncove.